Assessing the utility of the TET-1 hotspot detection and characterization algorithm for determining wildfire size and temperature. Issue 20 (17th October 2016) - Mitchell, Simon; Jones, Simon; Reinke, Karin; Lorenz, Eckehard; Reulke, Ralf
ABSTRACT: The detection and characterization of wildfires using satellite remote-sensing systems has improved considerably over the last 30 years, with daily, global coverage maintained by a number of satellite systems. The recent deployment of new satellite systems, such as Technologie-Erprobungs-Träger-1 (TET-1/Technology-Experiments-Carrier-1), with a higher spatial resolution than the current satellite sensing systems employed for global fire detection, presents an opportunity to investigate the utility and accuracy of the TET-1 detection and characterization algorithm in detecting fires over a range of areas and temperatures. In this study, simulated fire landscapes were generated based on varying fire area (1–100, 000 m 2 ) and fire temperature (450–1200 K) and passed through the TET-1 algorithm. The results indicate the TET-1 algorithm to estimate fire area to ±12% and fire temperature to ±3%, which implies that under the test conditions, the products generated by TET-1 have a low systematic error.